2009
DOI: 10.1158/0008-5472.can-08-2256
|View full text |Cite
|
Sign up to set email alerts
|

cIAP1, cIAP2, and XIAP Act Cooperatively via Nonredundant Pathways to Regulate Genotoxic Stress–Induced Nuclear Factor-κB Activation

Abstract: Various genotoxic agents cause monoubiquitination of NEMO/ IKK;-the regulatory subunit of IKB kinase (IKK) complexin the nucleus. Ubiquitinated NEMO exits from the nucleus and forms a complex with the IKK catalytic subunits IKKA and IKKB, resulting in IKK activation and, ultimately, nuclear factor-KB (NF-KB) activation. Thus, NEMO ubiquitination is a prerequisite for IKK-dependent activation of NF-KB. However, the IKK activation mechanism is unknown and the NEMOubiquitinating E3 enzyme has not been identified.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 45 publications
7
96
0
3
Order By: Relevance
“…The fact that no additional increase in apoptosis susceptibility was seen when the XIAP knockdown fibroblasts were treated with the Smac/ Diablo mimetics (Figure 7; Figure E3) suggests that the enhanced apoptosis observed in cells treated with the Smac/ Diablo mimetics is attributable to inhibition of XIAP and that XIAP inhibition is sufficient to regulate the apoptosis susceptibility of these cells. Although there was no significant difference in the expression of cIAP1 and cIAP2 between normal and IPF lung fibroblasts, the relative expression of these IAPs did correlate with XIAP in the IPF fibroblasts, suggesting that they are similarly regulated and may have a cooperative function with XIAP (50). However, these studies also suggest that any contribution to apoptosis resistance mediated by cIAP1 or cIAP2 was dependent on the presence of functionally intact XIAP.…”
Section: Discussionmentioning
confidence: 65%
“…The fact that no additional increase in apoptosis susceptibility was seen when the XIAP knockdown fibroblasts were treated with the Smac/ Diablo mimetics (Figure 7; Figure E3) suggests that the enhanced apoptosis observed in cells treated with the Smac/ Diablo mimetics is attributable to inhibition of XIAP and that XIAP inhibition is sufficient to regulate the apoptosis susceptibility of these cells. Although there was no significant difference in the expression of cIAP1 and cIAP2 between normal and IPF lung fibroblasts, the relative expression of these IAPs did correlate with XIAP in the IPF fibroblasts, suggesting that they are similarly regulated and may have a cooperative function with XIAP (50). However, these studies also suggest that any contribution to apoptosis resistance mediated by cIAP1 or cIAP2 was dependent on the presence of functionally intact XIAP.…”
Section: Discussionmentioning
confidence: 65%
“…These observations suggest that NEMO monoubiquitination is critical for NEMO export and ATM has additional downstream role(s) independent of NEMO phosphorylation. Jin et al [68] recently found that cIAP1 is the K277/K309-specific NEMO ubiquitin ligase involved in the genotoxic stress signaling. In consonance with the hypothesis that ATM mediates additional downstream function(s), a small fraction of activated ATM is exported to the cytoplasm of HEK293 cells in a NEMO-dependent manner, and associates with IKΚβ along with ELKS (a protein rich in glutamic acid, leucine, lysine and serine) [54].…”
Section: Nuclear Export Of Nemo and Atmmentioning
confidence: 99%
“…In addition to identifying cIAP1 as the ligase responsible for NEMO monoubiquitination, Jin et al [68] further found that TAK1 is required for NF-κB activation by VP16 and CPT, and that cIAP1 is also required for TAK1 activation by these agents. Thus, the authors placed cIAP1-mediated NEMO monoubiquitination upstream of TAK1 activation.…”
Section: Atm-dependent Ikk Activation In the Cytoplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…PIDD has been shown to translocate to the nucleus in response to genotoxic stress, and either PIDD or RIP1 depletion abolishes DNA damage-induced NF-B activation and NEMO sumoylation (11). Once sumoylated, NEMO is phosphorylated by ATM and monoubiquitinated potentially by the inhibitor of apoptosis protein cIAP1 in the nucleus (9,12,27). These events trigger the translocation of ATM and NEMO into the cytosol (27); however, the mechanism by which NEMO monoubiquitination leads to IKK activation is unknown.…”
mentioning
confidence: 99%